2015
DOI: 10.1002/ejic.201500668
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Features, Cytotoxicity, and Magnetic Properties of Colloidal Ferrite Spinel Co1–xNixFe2O4(0.1 ≤ x ≤ 0.9) Nanoparticles

Abstract: Colloidal ferrite spinel nanoparticles (Co x Ni 1-x Fe 2 O 4 ) were prepared by a microwave-stimulated Bradley technique under nonhydrolytic conditions. The effect of Ni 2+ doping on the structural properties was studied by powder XRD. The particle size, hydrodynamic size, and morphology were evaluated by transmission electron microscopy (TEM) and dynamic light scattering (DLS), which showed mean crystallite sizes of ca. 10 and 60 nm for powder and colloidal suspensions of Co x Ni 1-x Fe 2 O 4 , respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
2
14
1
Order By: Relevance
“…The chemical compositions of the Co 1– x Mn x Fe 2 O 4 nanoparticles were evaluated by using the SEM‐EDS technique, which showed good agreement between the planned and actual contents of the respective elements and their molar ratios (see Figure S1 in the Supporting Information). These results confirmed that the chosen synthetic approach allows for control of the composition with a wide range of concentration of Mn 2+ cations , …”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The chemical compositions of the Co 1– x Mn x Fe 2 O 4 nanoparticles were evaluated by using the SEM‐EDS technique, which showed good agreement between the planned and actual contents of the respective elements and their molar ratios (see Figure S1 in the Supporting Information). These results confirmed that the chosen synthetic approach allows for control of the composition with a wide range of concentration of Mn 2+ cations , …”
Section: Resultssupporting
confidence: 72%
“…The particles are spherical in shape and show a narrow size distribution. In fact, these features are characteristic for all ferrites synthesized by Bradley's reaction , . It has to be stressed that the selected area electron diffraction (SAED) image gives additional evidence for the structural purity of the final nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…5) [24,25]. Similar trend was observed in the case of Co 1-x Ni x Fe 2 O 4 samples prepared by microwave simulated Bradley synthesis [26].…”
Section: Methodssupporting
confidence: 67%
“…Magnetic properties of the Co 0.2 Mn 0.8 F 2 O 4 nanoparticles were studied in detail by us showing purely superparamagnetic properties 42. The exposure of C2 cells to both MF and MNPs resulted in a significant apoptotic cell death, as demonstrated by the calcein/propidium iodide staining (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The cobalt manganese ferrite nanoparticles were prepared accordingly to the previously described synthetic protocol 42. The Bradley microwave-stimulated method was used for the synthesis of Co 0.2 Mn 0.8 Fe 2 O 4 nanoparticles.…”
Section: Methodsmentioning
confidence: 99%